2018
DOI: 10.1002/smll.201803231
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Reshaping and Splitting of AgCl Nanocrystals under Electron Beam Illumination

Abstract: AgCl is photosensitive and thus often used as micromotors. However, the dynamics of individual AgCl nanoparticle motion in liquids upon illumination remains elusive. Here, using liquid cell transmission electron microscope (TEM), AgCl nanocrystals reshaping and splitting spontaneously in an aqueous solution under electron beam illumination are observed. It is found that the AgCl nanocrystals are negatively charged in the liquid environment, where the charge induces a repulsive Coulomb force that reshapes and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In addition, high-energy electron beams are frequently argued to exert complex effects towards specific samples upon intense illumination. Accordingly, in addition to rational experimental operations to avoid high-dose exposure of our interested areas to electron beam (see Methods), we assessed the impact of the electron beam by comparing different areas across the sample during the annealing experiment. It is found, however, a negligible electron beam effect on the whole process throughout nucleation stages of tungsten carbide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high-energy electron beams are frequently argued to exert complex effects towards specific samples upon intense illumination. Accordingly, in addition to rational experimental operations to avoid high-dose exposure of our interested areas to electron beam (see Methods), we assessed the impact of the electron beam by comparing different areas across the sample during the annealing experiment. It is found, however, a negligible electron beam effect on the whole process throughout nucleation stages of tungsten carbide.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zecěvićet al [108] showed that under STEM, the narrowly focused electron beam probe can elongate silica nanoparticles. Tian et al [109] showed that the electron beam can split AgCl nanocrystals, which reassemble when illumination terminates. As we will discuss later, often the electron beam effect is something that the experimentalist wants to avoid, with beam-induced damage changing the behaviour of the sample in adverse ways.…”
Section: The Growth Of More Complex Structuresmentioning
confidence: 99%
“…By developing and applying in situ liquid phase transmission electron microscopy, her group studies the nucleation, growth, and transformations of nanoscale materials and solid–liquid interfaces. Zheng published a Communication in Angewandte Chemie on tailoring transition‐metal hydroxides and oxides by photon‐induced reactions and a Full Paper in Small on the behavior of AgCl nanocrystals under electron beam illumination …”
Section: Awarded …mentioning
confidence: 74%